[OA188] Passive ion beam modulation techniques for particle therapy raster scanning facilities. (August 2018) - Ringbæk, Toke Printz; Weber, Uli; Santiago, Alina; Simeonov, Yuri; Wittig, Andrea; Iancu, Gheorghe; Mühlnickel, Werner; Granska, Leszek; Bassler, Niels; Engenhart-Cabillic, Rita; Zink, Klemens
Abstract : Purpose: Raster scanning particle therapy offers potentially very conformal treatments. Limitation are long irradiation times and a sensitivity to intra-fractional motion. Passive energy modulators with an inhomogeneous mass distribution broaden the width of the mono-energetic Bragg peaks and reduce the accelerator energy shifts needed to homogeneously cover the target and thus the irradiation time. A modulator in clinical use is the 1D ripple filter (RiFi). Newer 2D RiFis improve comparatively the filter mass distribution, reducing the overall lateral beam width with a further reduced irradiation time. For certain cases a 3D RiFi can be designed, which with one energy covers the whole target within seconds. All designs can be produced using 3D printing. Furthermore, porous materials could function like passive energy modulators. Methods: This work presents a general overview of these new modulators with focus on experimental data and treatment planning. We show carbon ion treatment plans with 1D and 2D RiFis for spheres in water, 8 NSCLC, 4 chordoma, and 3 prostate cases and proton plans for a 6 mm 2D RiFi compared to no RiFi for spheres and 9 NSCLC cases. A multi-ion facility was assumed and simulated. Baseline data for treatment planning were generated with the Monte Carlo code SHIELD-HIT12A and imported in the treatment planning systems TRiP98 and Eclipse. Results: Measured Bragg curves confirm the functionality of the new modulators for protons and carbon ions. For carbon ions, all plans yielded comparable dosimetric results in terms of plan homogeneity and conformity but with up to half the irradiation time for thicker RiFis. For protons, the RiFi offers a similar coverage as without with up to only one-fourth of the necessary accelerator shifts but were found to be most beneficial in treatment cases with reduced nozzle-to-treatment-isocenter distance. Plan homogeneity and conformity were slightly improved for thinner RiFis with RiFi performances increasing with penetration depth. Porous plates could be used as passive energy modulators and simultaneously function as range shifters, which placed close to the patients leads to reduced beam penumbras for low penetration depths. Conclusions: Passive energy modulators reduce the irradiation time in raster scanning particle therapy.